Plasticizers and bisphenol A, in packaged foods sold in the Tunisian markets: study of their acute in vivo toxicity and their environmental fate - Beltifa, Asma; Feriani, Anouar; Machreki, Monia; Ghorbel, Asma; Ghazouani, Lakhdar; Di Bella, Giuseppa; Van Loco, Joris; Reyns, Tim; Mansour, Hedi Ben (Environmental science and pollution research international, 2017)
Today, processed and packaged foods are considered as among the major sources of human exposure to plasticizers and bisphenol which migrate from plastic packing. In the present study, a wide range of food products sold on the Tunisian market such as grain and grain products, milk and dairy products, fats and oil, drink, fish, and sweets have been analyzed firstly in order to identify the presence of phthalates and bisphenol. Then, the identified chemical molecules were studied for their environmental fate and tested in vivo for its toxicity in mice models. The food products analyzed using GC-MS/MS indicated the presence of the benzyl butyl phthalate (BBP), dibutyl phthalate (DBP), bis(2-ethylhexyl) phthalate (DEHP), diisodecyl phthalate (DiDP), diisononyl phthalate (DiNP), and 1,2-cyclohexane dicarboxylic acid diisononyl ester (DINC) and which using UPLC-MS/MS demonstrated the presence of bisphenol A of all food products. However, compared to other phthalates, BBP was found at high concentrations in the puff pastry (123 mg/kg), milk (2.59 mg/kg), butter (1.5 mg/kg), yogurt (2.23 mg/kg), oil (6.94 mg/kg), water (0.57 mg/kg), candy 1 (2.35 mg/kg), candy 2 (0.81 mg/kg), orange juice (1.25 mg/kg), peach juice (1.26 mg/kg), fruit juices (0.4 mg/kg), and chocolate (0.884 mg/kg). The obtained data in vivo clearly showed that the acute administration of BBP caused hepatic and renal damage as demonstrated by an increase in biochemical parameters as well as the activities of plasma marker enzymes such as alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, lactate dehydrogenase, blood urea nitrogen, glucose, urea, creatinine, and uric acid when compared to the control group. By the same occurrence, the histopathological study revealed that BBP strongly modified the structure of hepatic and renal tissues. In addition, the plasticizers and BBP will therefore discharge via wastewater treatment plants in aquatic system and could reach marine organisms such as fish. We have followed the fate of BBP in bream Sparus aurata . In fact, chemical analysis showed the contamination of wild S. aurata by BBP from Sousse Coast (1.5 mg/kg) and wild S. aurata from Monastir Coast (0.33 mg/kg).